Pengaruh Etika Profesi, Kecerdasan Emosional dan Pengalaman Auditor Terhadap Kualitas Audit (Studi Empiris pada KAP di Kota Padang) Tahun 2021 - Putri, Meisy Dwi; Rina Asmeri; Meri Yani (Ekasakti Pareso Jurnal Akuntansi, 2024)
This study aims to determine and examine the effect of Professional Ethics and Emotional Intelligence and Auditor Experience on Audit Quality for Auditors at Public Accounting Firms in Padang City partially and simultaneously. This study uses an associative approach, namely research that aims to analyze the relationship between one variable and another. The population in this study are auditors who work at a Public Accounting Firm in Padang City using the Saturated Sanpling method. The results of this study are as follows: Partially Professional Ethics has an effect on Audit Quality, while Emotional Intelligence and Auditor Experience partially have no effect on Audit Quality. Simultaneously the Professional Ethics of Emotional Intelligence and Auditor Experience have an effect on Audit Quality.